Sosialisasi Penguatan Komunikasi Aparat Desa Untuk Mewujudkan Pelayanan Publik Yang Transparan - Jaka Maulana; Heru Wahyudi; Ulvia Fadilah; Rafif Prayata Nurbintan; Firzan Zakky (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Public service delivery at the village level requires effective organizational communication to ensure consistent internal coordination and transparent dissemination of service information to citizens. In Kramatwatu Village, Serang Regency, key challenges include unstructured internal communication among village officials, suboptimal external communication with the community, limited use of information media, and the absence of standardized communication flows that support service accountability. This community service program aimed to strengthen village officials’ internal and external communication as a prerequisite for more transparent public services and improved public trust. The program employed a participatory socialization approach through structured presentations, interactive discussions, case studies, role-play simulations of service communication, and guided reflection to formulate follow-up actions. The results indicate improved participants’ understanding of organizational communication, heightened awareness of service-information transparency, and emerging commitments to enhance communication channels (information boards, village social media, and deliberative forums) as well as initial steps toward developing a communication flow/SOP. These findings are significant as they highlight organizational communication strengthening as a practical foundation for sustaining improvements in village public service quality.